The quickest kid in Clarksville - Miller, Pat Zietlow (Chronicle Books, 2016)
Growing up in the segregated town of Clarksville, Tennessee, in the 1960s, Alta's family cannot afford to buy her new sneakers--but she still plans to attend the parade celebrating her hero Wilma Rudolph's three Olympic gold medals.